Analyzing Factors Affecting Customer Experience of Jenius Digital Banking in Indonesia - Cestlavie, Syfa; Nasution, Reza Ashari (Journal of Business and Management, 2020)
Indonesia sought opportunity in fintech and digitized financial development to improve access to financial services in Indonesia. Reflecting on one of the national banks in Indonesia, BTPN, that invented Jenius digital banking with its great customer experience, is successfully reaching 1,2 million users. Thus, there is an open opportunity for Indonesia to improve digitized financial development by enhancing the customer experience as the strategy. The research attempts to examine what is the most significant factor that affects positive customer experience in Jenius digital banking and the relationship of the accumulated experiences toward customer satisfaction and loyalty. Online questionnaire was conducted using Likert Scale designed for 229 respondents in Jakarta and Bandung with a purposive sampling method. The questionnaire was measured by SEM Analysis to explain the relationship between the exogenous and endogenous variables This study finds perceived value is the most significant factor of customer experience in Jenius digital banking. Another finding is the customer experience with accumulation of significant factors which are perceived value, convenience, service quality and employee-customer engagement positively affects customer satisfaction as well as customer satisfaction towards customer loyalty in Jenius digital banking. Keywords: Customer Experience, Customer Satisfaction, Customer Loyalty, Digital Banking, Perceived Value